The use of exhaled nitric oxide in the management of asthma. - Pavord, I; Shaw, D (2008)
It has recently become clear that airways disease associated with eosinophilic airway inflammation, but not other patterns of inflammation, is closely associated with favourable short-and long-term responses to corticosteroid therapy, irrespective of the clinical context in which it occurs. Moreover, a raised exhaled nitric oxide (FE(NO)) is a reasonable marker of eosinophilic airway inflammation, which has a number of advantages as a diagnostic and monitoring tool. In this review we outline essential background information on the use of FE(NO) in clinical practice and discuss some recent work evaluating the clinical value of this technique.